SOSIALISASI PENDIDIKAN REMAJA SEBAYA UNTUK MENCIPTAKAN GENERASI SEHAT DAN BERKUALITAS MELALUI KEGIATAN PENGABDIAN MASYARAKAT - Nur Avihani (Universitas Negeri Gorontalo, 2024)
Community service carried out by UKK KSR PMI Unit UIN K.H. Abdurrahman Wahid Pekalongan is based on the Tri Dharma of Higher Education. The partners in this community service activity are the people of Rogoselo Village who face the problem of unhealthy lifestyles, although several efforts have been made to improve these conditions. This problem needs to be resolved immediately because a healthy lifestyle is the key to a quality life. The purpose of this service is to increase the knowledge and awareness of the Rogoselo Village community, especially adolescents, about the importance of a healthy lifestyle through peer adolescent education. The methods used include socialization and adolescent posyandu activities, which are specifically designed to deliver information and healthy living practices to the community. The results of these activities are expected to create a healthy generation in Rogoselo Village, which in turn will make healthy lifestyles a sustainable habit in the community. In conclusion, youth peer education socialization can be an effective strategy to address the problem of unhealthy lifestyles in Rogoselo Village, thus supporting the creation of a healthy and quality generation